A Molecular Docking Study of Amyloid-Polysaccharide Composites: I. Interactions with Polyphenols - Trusova, Valeriya; Malovytsia, Uliana; Zhytniakivska, Olga; Gorbenko, Galyna (East European Journal of Physics, 2026)
Filamentous protein aggregates, amyloid fibrils, currently attract considerable interest as a prospective nanomaterial for a variety of biomedical and industrial applications. Among their advantages are biocompatibility, high stability and mechanical strength, self-assembly capability, etc. The integration of other biopolymers such as polysaccharides into amyloid matrix enables creating novel nanomaterials with improved mechanical characteristics and higher loading capacity for biologically active compounds. In the present study we employed the molecular docking technique to ascertain the molecular details of the interactions between the lysozyme amyloid fibrils and a series of polyphenolic compounds including curcumin, gallic acid, salicylic acid, quercetin, resveratrol and sesamin, and to explore the effect of polysaccharide chitosan on such kind of interactions. It was shown that curcumin in enol form has the highest binding affinity for fibrillar lysozyme, while the lowest affinity was observed for salicylic acid. The binding sites for curcumin, gallic acid, quercetin, resveratrol and sesamin appear to occupy the groove on the wet fibril surface, while salicylic acid binds to the dry surface of the fibril. The interfacial amino acid residues in the fibril complexes with polyphenols and chitosan are identified. Chitosan was found to display the ability to interact with polyphenolic compounds within amyloid matrix, resulting in the enhancement of polyphenol binding. The data obtained provide a basis for further designing and experimental testing of the amyloid-chitosan nanocomposites loaded with polyphenols.